Annual and seasonal fructuations of bare soil temperature values In Thessaloniki-Greece - GOUTSIDOU, Y.A.; MAKROGIANNIS, T.J.; FLOCAS, A.A.; SAHSAMANOGLOU, C.S. (MAUSAM, 1992)
The data. used for this study form the time series of the annual and seasonal fluctuations of bare soil temperature values In Thessaloniki-Greece. The mean arrival value IS 20°C with a standard deviation of 1 .3°C. The winter is the most variable season. The analysis of these time series has shown that there were notable spells of years with values above or below the normal one. Negative trends were observed for the annual and seasonal values with the exception of winters. The well known QBO was found in the annual and spring time series.